The Role of Teachers in the Discipline Character Habituation of Students at Muhammadiyah Elementary School: Peran Guru dalam Pembiasaan Karakter Disiplin Siswa di Sekolah Dasar Muhammadiyah - Antika, Afrelya Rindi; Supriyadi, Supriyadi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe the habituation of students' disciplined characters and the role played by teachers in habituation of students' disciplined characters. The object of the research was conducted at Muhammadiyah 3 Ikrom Elementary School, Sidoarjo. The research subjects were 2 third grade teachers. Data was collected using observation, interview and documentation techniques which were then analyzed using the Miles model, namely condensation, data presentation, drawing conclusions and verification. The results showed that the habituation of the student's disciplinary character was carried out by the teacher by applying the my point system, welcoming students in the morning, verbally reminding them, greeting and greetings when they met, and getting used to Dzuha prayers, and muraja'ah every morning. The teacher's role in familiarizing the disciplined character in doing assignments, preparing school needs, attendance, and obeying school rules, the teacher acts as a teacher, mentor, counselor, evaluator, model, and creator.